2007
DOI: 10.1113/jphysiol.2007.131722
|View full text |Cite
|
Sign up to set email alerts
|

NHE3 inhibition by cAMP and Ca2+ is abolished in PDZ‐domain protein PDZK1‐deficient murine enterocytes

Abstract: The PDZ-binding protein PDZK1 (NHERF3/CAP70/PDZ-dc-1) in vitro binds to NHE3, but its role in the regulation of NHE3 activity in native enterocytes is unknown. This study was undertaken to understand the physiological role of PDZK1 in regulating NHE3 activity in native murine colonic enterocytes. NHE3 transport rates were assessed fluorometrically in BCECF-loaded colonic crypts in the NHE3-expressing cryptal openings by measuring acid-activated, Na + -dependent, Hoe 642-insensitive proton efflux rates. NHE3 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 47 publications
3
102
1
Order By: Relevance
“…It was shown previously that the Cl -/HCO 3 -exchanger SLC26A3 and NHE3 are inhibited by the pathological increase of intracellular Ca 2+ [6,26]. In our experiments, CDC induced a dose- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 the release from the ER via IP 3 R and/or RyR or Ca 2+ entry from the extracellular space [32,14,13] [26].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was shown previously that the Cl -/HCO 3 -exchanger SLC26A3 and NHE3 are inhibited by the pathological increase of intracellular Ca 2+ [6,26]. In our experiments, CDC induced a dose- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 the release from the ER via IP 3 R and/or RyR or Ca 2+ entry from the extracellular space [32,14,13] [26].…”
Section: Discussionmentioning
confidence: 91%
“…The activities of the different NHE isoforms are extracted by using the isoform selective NHE inhibitor HOE-642. The isoform selectivity of HOE-642 is dose-dependent, 1µM HOE642 inhibits NHE1 whereas 50µM HOE642 inhibits both NHE1 and 2 but not NHE3 [2,6]. The activities (A) of NHE isoforms can be calculated from the recoveries (R) as follows: …”
Section: Measurement Of Nhe Activitiesmentioning
confidence: 99%
“…Furthermore, colonic surface cells from PDZK1 knock-out mice show loss of calcium inhibition of NHE3 (34). In these colonic surface cells NHE3 and DRA are coexpressed (32).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun evaluating the effect of NHERF3 on mouse intestinal Na ϩ and Cl Ϫ transport. Basal electroneutral sodium absorption was decreased by Ͼ40% in the NHERF3 null mouse jejunum (21) and by Ͼ80% in the colon (22). In addition, Cinar et al (22) demonstrated that cAMP and [Ca 2ϩ ] i inhibition of NHE3 activity was abolished in the NHERF3 null mouse colon.…”
mentioning
confidence: 96%